Innovation Performance of Large Contractor in Indonesia: Influencing Factors and its Impact on Firm's Performance. (2017) - Julison, B.; Wardani, S.P.R.; Wibowo, M.A.
Abstract: This study aims to determine: factors that influence innovation performance in large contractor firm, and impact of innovation performance on firm's performance. The firm's performance may include: project performance, performance of firm's competitiveness, firm's competitive advantage, and firm's sustainable competitive advantage. Factors that influence innovation performance are classified into 3 groups: driving factor, internal factor and external factor. Data collected by a questionnaire survey sent to 452 companies (10% of the population). Only 248 questionnaires (5.5% of the population) that returned and can be analyzed further. The questionnaire use a 1-4 Likert scale as a measuring tool. Data were analyzed through three stages: descriptive statistics analysis to determine the tendency of responds, Spearman's rank correlation analysis to eliminate indicators that less than 0.50, and analysis of partial least squares of structural equation modeling to determine the magnitude of the effect of the variables studied. This study result are: 1) driving factors and internal factors positively affect innovation performance, while external factors affect negatively, 2) the influence of internal factors and driving factors at almost the same level, and 3) innovation performance affects firm's sustainable competitive advantages through project performances, performance of the firm's competitiveness and firm's competitive advantages.